2019
DOI: 10.1002/adem.201900359
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Step Nitriding Behavior of Pure Iron with a Nanostructured Surface Layer

Abstract: A two-step gas nitriding treatment (280 C for 2 h plus 550 C for 6 h) is designed for pure iron with a nanostructured surface layer induced by surface mechanical attrition treatment (SMAT). The microstructure and surface properties of the SMAT sample after two-step nitriding treatment are investigated in comparison with those of the SMAT sample after single-step nitriding treatment (550 C for 6 h). Experimental results show that a much thicker compound layer (up to 25 μm in thickness) is generated on the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Tong et al 23 proved that nitriding at low temperature can effectively produce a high hardness surface layer by means of surface nanocrystallization treatment. Other studies also proved that it is feasible to improve surface properties by the combination of surface mechanical treatment and low-temperature diffusion treatment 24,25 . Thus, the effect of USDR plus OBD at lower diffusion temperature on fatigue properties should be further investigated.…”
Section: Residual Stressmentioning
confidence: 94%
“…Tong et al 23 proved that nitriding at low temperature can effectively produce a high hardness surface layer by means of surface nanocrystallization treatment. Other studies also proved that it is feasible to improve surface properties by the combination of surface mechanical treatment and low-temperature diffusion treatment 24,25 . Thus, the effect of USDR plus OBD at lower diffusion temperature on fatigue properties should be further investigated.…”
Section: Residual Stressmentioning
confidence: 94%
“…(1) Nitriding time: The pretreatment of surface mechanical nano-crystallization can shorten the nitriding time of gas nitriding to 70%. Sun et al [127] performed mechanical grinding on the surface of pure iron and then carried out nitriding treatment in an ammonia atmosphere. It was found that the nitriding depth of the SMAT sample was greater than that of the untreated sample, and the nitriding time was also reduced by about 30%.…”
Section: Effect Of Surface Mechanical Nano-crystallization On Nitridi...mentioning
confidence: 99%
“…In this study, ε phase nitride, which had not been transformed and left a small amount, was not a significant problem to confirm whether the γ' phase nitride of thick layer, which was formed by 2stage gas nitriding, was able to improve fatigue strength compared to γ' phase nitride formed at once. According to the literature [12,19,20], however, it was recorded that the ε phase formed in the first stage was mostly transformed into γ' phase in the second stage for a short time. Nevertheless, this study showed different results than expected that ε phase formed in the first stage would be completely transformed into the γ' phase in the second stage during 2-stage gas nitriding.…”
Section: Phase-transformation Gas Nitridingmentioning
confidence: 99%
“…Therefore, this study is intended to investigate the effect on fatigue strength by forming thick iron nitride consisted of γ phase through 2-stage gas nitriding. 2-stage gas nitriding is a technique in which an iron nitride layer consisting of ε phase, which is grown to be relatively thick compared to that consisting of γ phase at the same time, is first formed on the surface, and then iron nitride consisting of ε phase is phase-transformed to γ phase by controlling K N [12,19,20]; i.e., it was intended to investigate how the fatigue strength of iron nitride consisting of γ phase, which was phase-transformed in ε phase through 2-stage gas nitriding, and that of iron nitride consisting of γ phase, grown at one time through phase-controlled gas nitriding, are compared.…”
Section: Introductionmentioning
confidence: 99%